Thermal variation influences the transcriptome of the major malaria vector Anopheles stephensi - Ashutosh K. Pathak; Shannon Quek; Ritu Sharma; Justine C. Shiau; Matthew B. Thomas; Grant L. Hughes; Courtney C. Murdock (Communications Biology)
Abstract The distribution and abundance of ectothermic mosquitoes are strongly affected by temperature, but mechanisms remain unexplored. We describe the effect of temperature on the transcriptome of Anopheles stephensi, an invasive vector of human malaria. Adult females were maintained across a range of mean temperatures (20 °C, 24 °C and 28 °C), with daily fluctuations of +5 °C and −4 °C at each mean temperature. Transcriptomes were described up to 19 days post-blood meal. Of the >3100 differentially expressed genes, we observed shared temporal expression profiles across all temperatures, suggesting their indispensability to mosquito life history. Tolerance to 20 and 28 ( + 5°C/−4°C) was associated with larger and more diverse transcriptomes compared to 24 ( + 5 °C/−4 °C). Finally, we identified two distinct trends in gene expression in response to blood meal ingestion, oxidative stress, and reproduction. Our work has implications for mosquitoes’ response to thermal variation, mosquito immune-physiology, mosquito-malaria interactions and the development of vector control tools.